2007
DOI: 10.1139/h07-007
|View full text |Cite
|
Sign up to set email alerts
|

Muscle oxygenation during prolonged electrical stimulation-evoked cycling in paraplegics

Abstract: This study investigated cardiorespiratory responses and muscle oxygenation during prolonged electrical stimulation (ES)-evoked leg cycling in individuals with paraplegia (PARA). Four PARA and 6 able-bodied (AB) persons participated in this study. Subjects performed 10 min of passive cycling and 40 min of active cycling (PARA, ES cycling; AB, voluntary cycling) at workloads selected to elicit an equivalent oxygen uptake between groups. Cycling power output, cardiorespiratory responses, mechanical efficiency, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 30 publications
0
19
2
Order By: Relevance
“…123,124 Evidence that did not adhere either to randomization or controlling the treatment has explored FES-evoked exercise responses among persons with tetraplegia 38,41,72,125 ; children with SCI 126 ; and an individual's fatigue responses, 23,127 gas exchange kinetics during exercise involving aerobic and anaerobic metabolism, [128][129][130][131][132] and muscle deoxygenation and leg metabolism. 29,76,82,101,133 A consistent finding in this less rigorous research has been the observation that work rate and load of exercise are important determinants of metabolic responses 55,73,110,134 and, in particular, the power output production of the legs. 42,64,65,130 In general, and in agreement with the prior two categories of physiological outcomes, the empirical evidence lends support to positive metabolic responses and increased aerobic fitness for people with SCI who participate in FES-induced exercise training programs.…”
Section: Metabolic Responses and Aerobic Fitnessmentioning
confidence: 89%
See 1 more Smart Citation
“…123,124 Evidence that did not adhere either to randomization or controlling the treatment has explored FES-evoked exercise responses among persons with tetraplegia 38,41,72,125 ; children with SCI 126 ; and an individual's fatigue responses, 23,127 gas exchange kinetics during exercise involving aerobic and anaerobic metabolism, [128][129][130][131][132] and muscle deoxygenation and leg metabolism. 29,76,82,101,133 A consistent finding in this less rigorous research has been the observation that work rate and load of exercise are important determinants of metabolic responses 55,73,110,134 and, in particular, the power output production of the legs. 42,64,65,130 In general, and in agreement with the prior two categories of physiological outcomes, the empirical evidence lends support to positive metabolic responses and increased aerobic fitness for people with SCI who participate in FES-induced exercise training programs.…”
Section: Metabolic Responses and Aerobic Fitnessmentioning
confidence: 89%
“…The whole-body metabolic responses of SCI individuals during leg exercise are quite different from the able-bodied population due to their considerably smaller leg muscle mass and the inherent differences of FESevoked muscle contractions compared to voluntary muscle activation. 37,101,102 SCI does not affect the ability of the central nervous system to elicit metabolic responses during FES exercise, 69 particularly those dependent upon baroreflex activity during voluntary effort. 103 However, some studies that have investigated submaximal and graded FES exercise have revealed different metabolic responses among SCI subjects.…”
Section: Metabolic Responses and Aerobic Fitnessmentioning
confidence: 94%
“…Cardiorespiratory and muscle oxygenation responses to electrical stimulation-evoked leg cycling were measured using NIRS in patients with paraplegia [53]. The study observed that equilibrium between oxygen demand and delivery was reached during prolonged electrical cycling, despite the lack of neural adjustment of leg vasculature in the paralysed lower limbs.…”
Section: (D) Examples Of Recent Advanced Near-infrared Spectroscopy Amentioning
confidence: 99%
“…[ 10 ] As such, muscle oxidative metabolism during FES-evoked exercise is physiologically interesting (and infrequently investigated in person with SCI), because the muscle metabolic pattern during FES is dissimilar to voluntary contractions and may vary under different stimulation protocols. [ 11 , 12 ]…”
Section: Introductionmentioning
confidence: 99%